“Ukrainian wave” in the context of music life in modern Switzerland - Vardanyan, Olga (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. The struggle of the Ukrainian people for freedom and independence has caused a great international wave of sympathy and, at the same time, interest in Ukraine and its artistic heritage. Intensification of cultural communication with other countries actualizes the need to understand the mechanisms of cultural life in Europe, the USA, other countries of the West and East. The study of the audience of classical music concerts is important because the listener is the final consumer of the music product. Studying the mechanisms of organizing a large international festival on the example of Lucerne Festival is important and promising. Main objectives of the study. To highlight the problem of perception of Ukrainian music by the Swiss public and to describe the ways to overcome it in the context of the mechanisms of organization of musical life in Switzerland. Methodology. The research is based on general scientific empirical (observation, description) and theoretical (generalization, comparison) methods. Statistical and sociological methods are used to identify patterns in the change of preferences of the European public in recent years. Results and conclusions. The research summarized the experience of foreign scientists in studying the problem of audience aging. Some theories such as the theory of generations and the cohort effect are highlighted. Approaches to attracting new generations to the audience of classical music concerts are generalized. Problem areas in the perception of Ukrainian art by the European audience are identified and ways to overcome the problem are proposed. Prospects for further research. The actual lack of research on the third link of the triad "composer — performer — listener" and the relevance of the object promotes further research in this area. Particular importance is the focus on foreign listeners, the search for ways to "translate" the meanings underlying the Ukrainian artistic product.